2020
DOI: 10.3889/oamjms.2020.5491
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Orthopedic Services in Two Indonesian Tertiary-referral Hospitals during the Coronavirus-19 Pandemic

Abstract: BACKGROUND: Many countries report decreasing on the number of hospital visit even on the emergency cases. AIM: This study aims to reveal the important data on how big the impact of coronavirus-19 pandemic on orthopedic services in two Government’s tertiary-referral hospitals. METHODS: This research is a comparison study to measure the trend of orthopedic services, the monthly orthopedic surgical load and outpatient visit were examined during the period of March to May 2020 (the early pandemic perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In the shoulder, upper arm, forearm, wrist, hand, and femur groups, there was a significant reduction in cases. These results are in line with a study that showed a considerable difference in the number of outpatient visits and orthopedic surgery procedures during the beginnings of the pandemic relative to the time before the outbreak [19], [20], [21], [22], [23]. In contrast, the decrease was not significant in the lumbar spine, pelvis, lower leg, and ankle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the shoulder, upper arm, forearm, wrist, hand, and femur groups, there was a significant reduction in cases. These results are in line with a study that showed a considerable difference in the number of outpatient visits and orthopedic surgery procedures during the beginnings of the pandemic relative to the time before the outbreak [19], [20], [21], [22], [23]. In contrast, the decrease was not significant in the lumbar spine, pelvis, lower leg, and ankle.…”
Section: Discussionsupporting
confidence: 91%
“…COVID-19 pandemics have caused substantial disruptions to orthopedic and trauma services with more pronounced reductions in elective surgery [24]. Early data from Indonesia revealed dramatic declines in the number of surgery loads in March, April, and May 2020 [19]. Pediatric orthopedic practice has also been seriously affected, as the number of elective surgeries and outpatient clinics have had to be reduced [18].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first confirmed case of COVID-19 in Indonesia in early March 2020, all aspects of medical services in Indonesia have been affected [8]. It is ranged from primary care service until surgery service [9], [10], [11]. There were several previous papers that reported the effect of the COVID-19 pandemic to THA/TKA surgical service from other countries [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in surgical caseload for orthopedic trauma has been reported in Singapore [6]. A short study conducted in Indonesia found a noticeable difference in the number of outpatient visits and orthopedic surgery procedures during the early pandemic era compared to before the pandemic [7].…”
Section: Introductionmentioning
confidence: 99%